Penggunaan Metode Resitasi dalam Meningkatkan Kualitas Pembelajaran Fiqih di MTS Madrasatul Qur’an Tebuireng Jombang - Umi Khumairoh Mawaddah; Iva Inayatul Ilahiyah (Al-Liqo: Jurnal Pendidikan Islam, 2021)
Learning is the activity of delivering knowledge given by educators to students which aims to achieve educational targets. From this learning activity can be determined whether or not the goals of education are achieved. The use of inappropriate methods can cause problems during learning activities. The material that has been delivered by the educator will be in vain because students cannot digest the lesson effectively. The use of the recitation method in learning activities can increase the effectiveness of learning. The purpose of this study is to explain the use of the recitation method or the most effective assignment if applied in MTs Madrasatul Qur'an because it trains students to think and be responsible when carrying out the obligations presented by the educator. Besides directing students to think and be responsible for using the recitation method, it also trains students' independence so that students become more active because they seek or explore knowledge on their own without assistance from the educators. So that the learning objectives are easily achieved and will produce quality learning. In this study the approach used is descriptive qualitative. And the type of research used is field research or field research and uses qualitative research methods. The results of this study indicate that the recitation method can improve the quality of Fiqh learning, it can be seen from the students who are very enthusiastic about participating in learning activities and the increase in the value of student learning outcomes can be seen from the student assignment scores above the KKM score.